Group Difference Cordial Labeling of some Ladder related Graphs (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Let  be a graph. Let  be a group. For  let  denotesthe order of in  Let  be a function. For eachedge assign the label Let denote  the number of vertices of having label  under  Alsorespectively denote the number of edges labeled withand not with .Nowis called a group difference cordial labeling if for every and . A graph which admits a group difference cordial labeling is called group difference cordial graph. In this paper we fix the groupas the group which is the group of fourth roots of unity, that is cyclic with generators                                 We prove that Open ladder, Slanting ladder and further characterized  .